VD_FINDINFO Jug / 2024 / 127 vom 11. Oktober 2023 - VD Tribunal cantonal (2023)
ADMISSION PARTIELLE, SURSIS À L'EXÉCUTION DE LA PEINE, FIXATION DE LA PEINE | 34 CP, 42 al. 1 CP, 399 al. 3 CPP (CH), 423 al. 1 CPP (CH), 115 al. 1 let. b LEI